Fermentação ruminal e produção de metano em bovinos alimentados com feno de capim-tifton 85 e concentrado com aditivos - Rivera, Astrid Rivera [UNESP]; Berchielli, Telma Teresinha [UNESP]; Messana, Juliana Duarte [UNESP]; Velasquez, Paula Toro [UNESP]; Franco, Ana Vera Martins; Fernandes, Lauriston Bertelli (My University, 2010)
The objective of this study was to evaluate the effect of monensin, yeast complex, unsaturated fatty acids and amino acids on dry matter and nutrient intake, total and partial digestibility and ruminal parameters of ruminal fermentation (pH, ammonia nitrogen concentration and short chain fatty acids), the protozoa population and methane production. Six castrated steers, body weight 530 ± 15 kg were used, receiving yeast complex, polyunsaturated fatty acids and amino acids (5 g/dia), monensin (5 g/dia), caulim (5g/dia, used as control), added to a diet consisting of Tifton 85 (Cynodon spp.) hay and concentrate at 80:20. A randomized complete block design was used to analyze and a split-plot design was used to analyze ruminal fermentation and methane production. The intakes were influenced by monensin in the diet, and no difference was observed among the additives. The dry matter and nutrients digestibilities, were not influenced by supplementing with additives. The acetate:propionate ratio in the animals fed the diet with monensin was smaller than in those that received the yeast complex and polyunsaturated fatty acids and amino acids, decreasing the energy loss in the form of methane. The pH and ammonia nitrogen concentration were adequate to microbial growth. The methane concentration was not altered with the use of the amino acids tested. © 2010 Sociedade Brasileira de Zootecnia.
Ruminal fermentation and methane production of cattle fed Tifton 85 grass hay and concentrate with additives
Keywords: Insatured fatty acid; Methane; Monensin; Yeast cells